2021
DOI: 10.1002/jctb.6746
|View full text |Cite
|
Sign up to set email alerts
|

The automatic and high‐throughput purification and enrichment of microalgae cells using deterministic lateral displacement arrays with different post shapes

Abstract: BACKGROUND: Microalgae is an important natural resource, which has been used in various fields such as health care, chemical industry, clean energy, and environmental protection. However, microalgae samples are prone to be contaminated by bacteria, impurities, or other hybrid microalgae species. Enrichment and purification must be carried out before further research and utilization.RESULT: Herein, a microfluidic microalgae enrichment and purification system based on the principle of deterministic lateral displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Each micropillar was an equilateral triangle with a side length of 30 µm. Yanjuan Wang et al [ 38 ] designed two different shapes of micropillars, circular and triangular. The performance of the two chips was analyzed in terms of stability, flux, recovery efficiency, purity, and enrichment coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…Each micropillar was an equilateral triangle with a side length of 30 µm. Yanjuan Wang et al [ 38 ] designed two different shapes of micropillars, circular and triangular. The performance of the two chips was analyzed in terms of stability, flux, recovery efficiency, purity, and enrichment coefficient.…”
Section: Methodsmentioning
confidence: 99%
“…b Adjusted pillar gaps of a DLD array 63 . c Triangular array for microalgae enrichment and purification 72 . d I-shaped, T-shaped, and L-shaped rotation-induced DLD separation 15 .…”
Section: Different Biological Micro-object Separation Microfluidic Sc...mentioning
confidence: 99%
“…Wang et al fabricated a triangular DLD array and a circular array for microalgae enrichment and purification for the first time and revealed that the triangular post array has a better performance over the circular array (Fig. 2c ) 72 . Rectangular, L-shaped, and I-shaped pillars have also been well studied by both numerical and experimental methods, showing an even greater decrease in critical diameter 15 , 73 75 .…”
Section: Different Biological Micro-object Separation Microfluidic Sc...mentioning
confidence: 99%
See 2 more Smart Citations